Types of Lexical Cohesion in Song Lyrics of The Greatest Showman Movie Soundtrack Album - Sebrina Wijayanti; Zahrida Zahrida; Mulyadi Mulyadi (Universitas Bengkulu, 2022)
This research aim to finds out types and the most dominant of lexical cohesion used in the song lyrics The Greatest Showman movie soundtrack album. The methodology of this research is descriptive quantitative method. The objects of this research are 5 song lyrics in The Greatest Showman movie soundtrack album namely “A Million Dreams, Never Enough, This Is Me, The Other Side and Rewrite The Stars. The data were collected by using observation sheet and table checklist. The collected data were analyzed by using statistical formula. The result of this research showed that:1. All types of lexical cohesion namely repetition, synonym, superordinate, general words and collocation were found in the song lyrics The Greatest Showman movie soundtrack album. 2. The most dominant type of lexical cohesion is Repetition. It was concluded that repetition occurred dominantly because the composer or writer want to tell the reader and listener that the focus of discourse is in the words which have been repeated to emphasize certain meanings in order to attract attention listeners and to enhance beauty in songs.